Brown Bear, Brown Bear, What Can You See? Exploring the Tension Between Strategic Choices and Claimants’ Voices in Environmental Litigation in the EU - Reilly Anne Dempsey Willis (German Law Journal)
This paper poses an important challenge to the growing trend of strategic environmental litigation in the EU: when making strategic choices about bringing, framing, and litigating claims, what becomes more important—being heard through strategically critical procedural choices or being true through ensuring that rights holders and the environment remain at the forefront of decision-making? There are many legal hurdles to bringing environmental claims and it is possible that the voice of the environment and those most adversely affected by its degradation is lost in the strategic legal decision-making. This study uses a small number unstructured scoping interviews with practitioners active in bringing litigation to the CJEU to inductively analyse voice and representation in strategic environmental litigation. This initial research indicates that there are areas which should be further explored. First, all of the practitioners brought up the issue of access to resources. This raises concerns about potential elitism. Second, practitioners highlighted that there are numerous strategic choices made during case selection and framing which could affect how voices are heard. Finally, practitioners felt strongly that admissibility rules have a negative impact on claimants’ voices. Challenges in legal standing and establishing individual harm or direct concern have an enormous impact on what claims are heard and how they are heard.